Pengaruh Profitabilitas, Solvabilitas, Ukuran Perusahaan, Umur Perusahaan, Ukuran KAP, Kepemilikan Institusional, dan Independent Commissioner terhadap Audit Report Lag - Catheryn Iona Nelson; Yoga Andriawan; Haryono Umar (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2022)
The purpose of this study is to obtain an empirical evidence and analyze factors that affecting audit report lag. The independent variables in this study are profitability, solvability, company size, age of company, audit firm size, institutional ownership, and independent commissioner. While the dependent variable in this study is audit report lag. The company used in this research is manufacturing companies that listed on the Indonesian Stock Exchange (IDX) over three years period from 2017 to 2019. The number of research samples is 240 firm years data. This research is using multiple, regression method to examine the effect of independent variables to the audit report lag as the independent variable. The result of this study shows that profitability, company size, and age of company have an effect, on audit report lag while solvability, age of company, audit firm size, institutional ownership, and independent commissioner have no effect on audit report lag.